SEASONAL CHANGES IN TESTES SIZE, FRESH AND POST-THAWING SEMEN CHARACTERISTICS, SERUM TESTOSTERONE LEVEL, AND PHOSPHOLIPASE A ACTIVITY IN GURCU MALE GOATS - R. Kulaksz; U. Ç. Ar; M. Kuru; S. Yldz; N. C. Lehimcio lu; Y. Öztürkler; E. Ataki_i (Journal of Animal and Plant Sciences, 2019)
The aim of current investigation was to evaluate seasonal changes in the testicular measurements, fresh and post-thawing spermatological characteristics, serum testosterone (T) levels in Gurcu goats. Moreover, seminal plasma phospholipase A2 activity levels were determined. Four adult Gurcu male goats (2-3 years old) were used as semen donor and ejaculates (n=113) from these goats were weekly collected with artificial vagina in the presence of natural estrus or estrogened female fantom during breeding season (BS, September-February) and non breeding season (NBS, March-August), respectively. Moreover, jugular blood was collected and serums were separated to determine Testesterone level during BS and NBS.  All andrologic parameters, except testes width (P<0.05), were not changed statistically during BS and NBS in Gurcu bucks. It was determined that ejaculate volume (1.27±0.05 vs 0.76±0.04mL; P=0.001), fresh progressive sperm motility (80.39±1.00 vs 74.43±2.26%; P=0.019) were significantly higher in BS compared to NBS, respectively. However, sperm concentration (3.93x109 vs 2.48x109 spermatozoa/mL; P=0.001) was interestingly higher during NBS compared with BS, although total number of sperms per ejaculate were similar during BS (3.03x109 spermatozoa/ejaculate) and NBS (2.93x109 spermatozoa/ejaculate), P>0.05. Also there was no differences in post-thaw progressive sperm motility between BS and NBS (25.0±2.86 vs 19.32±2.55%; P=0.145). T did not any show significant change between BS and NBS (13.44 ±2.37 vs. 13.06±1.18 ng/mL). Although seasonal changes were observed in andrologic parameters, fresh and post-thawing spermatozoa in Gurcu bucks, this effect was limited.
Keywords: Gurcu goats; phosholipase A; seasonal variation; semen characteristics; testes; testosterone